Population changes in Gharial (Gavialis gangeticus) vary spatially in Chitwan National Park, Nepal - Khadka, Bed Bahadur; Bashyal, Ashish; Griffith, Phoebe (Reptiles & Amphibians, 2024)
Gharials, large crocodilians found only in South Asia, are widely seen as a flagship species for river conservationin Nepal, especially in Chitwan National Park, where a headstart program has supplemented the populationsince 1981. The population has shown signs of recovery only in the last decade, so continued monitoring of populationtrends is vital for conservation. We conducted annual winter population surveys for gharial in Chitwan between 2017and 2022, during which we also characterized riverbank substrate availability and basking preferences. We documentedpotential threats to the species in Chitwan throughout the year. Overall, we counted an increasing number of Gharialsin Chitwan; however mixed-effects modelling of Gharial encounter rate showed that increasing encounters rates are notevenly distributed throughout available habitat, with some river stretches having stable or decreasing trends. Encounterrates on the Rapti River increased in all transects, compared to more variable results on the Narayani River, likelyattributable to higher levels of human disturbance and the impact of captivity on habitat selection. Fewer Gharials wereseen in transects with high levels of disturbance due to sand mining and the extraction of river substrates, highlightingthis threat as a major concern. Regular reports of bycatch in illegal gillnets was the major observed source of mortality.A lack of an increasing population trend in the stretch above a large barrage suggests that recruitment is minimal inthis area, and the dam likely has a negative impact on upstream Gharial recruitment. We cautiously suggest that theChitwan population is recovering, but that recovery is hampered by threats, especially substrate extraction, illegal gillnetfishing, and river fragmentation by a dam.